Consistent acoustic size estimation of sperm whales using clicks recorded from unknown aspects - Teloni, Valeria; Zimmer , Walter M. X.; Wahlberg, Magnus; Madsen, Peter T. (J. Cetacean Res. Manage., 2023)
The multipulse structure of sperm whale clicks offers a unique way to acoustically estimate body length, as the inter-pulse intervals within the clicks relate to the two-way travel time within and thereby to the size of the hypertrophied nose in this species. Despite its large potential to allow the estimation of length acoustically, the technique has only been used in a few studies to assess the length composition of sperm whale populations. Its limited use may relate to the fact that only some clicks within a click series normally display the regular multipulsed structure required for size estimation. The inter-pulse intervals of usual clicks vary with the recording aspect to the clicking whale and the pulse delays are not necessarily directly related to the length of the spermaceti organ. To overcome these difficulties, a method is provided to estimate sperm whale body lengths, based on averages of cepstra derived from a large number of clicks recorded from whales in unknown recording aspects. This study shows that the two-way travel time in the spermaceti organ can consistently be estimated by a peak in the averaged cepstra when a large number of clicks are analysed. This method is shown to give a consistent estimation of the size of the spermaceti organ when recording the whale in an unknown orientation and also when recordings are heavily influenced by surface reflections.